105 A presentation resembling transient global amnesia with underlying tako-tsubo cardiomyopathy and multifocal ischaemic stroke (with restricted diffusion in the left mesiotemporal lobe). (29th July 2019) - Lefever, Kristen; Tyson, Chloe; Shelley, Lisa; Schweitzer, Daniel; Swayne, Andrew
Abstract : Introduction: We present a case of a 65 year-old female with a presentation resembling transient global amnesia (TGA) with investigations revealing a Tako-tsubo cardiomoyopathy and multifocal punctate areas of restricted diffusion consistent with ischaemic stroke. Methods: Single case report. Results: A 65 year-old female presented altered behaviour with anterograde amnesia consistent with an episode of TGA. There was no clearly identifiable stressor to provoke this episode. The TGA-like symptoms persistent for 12 hours before the patient made a full recovery. During the presentation the patient complained of chest pain with elevated troponin. Cardiac investigation was notable for mild left ventricular dilation with mid- and apical hypokinesis on transthoracic echocardiogram and a normal coronary angiogram consistent with Tako-tsubo cardiomyopathy. Magnetic resonance imaging of the brain revealed multifocal infarcts including punctate foci of restricted diffusion within the left mesiotemporal lobe. Conclusion: This case is notable as it is rare to have a combined presentation with TGA-type symptoms with Tako-tsubo cardiomyopathy and multifocal ischaemia stroke. 1 This is the first clinical case presentation involving the aforementioned triad and mesiotemporal lobe restricted diffusion. We hypothesise that the Tako-tsubo cardiomyopathy acted as the triggering event and the mesiotemporal lobe involvement caused the TGA-like symptoms thereby accounting for the clinical presentation and investigation findings. As mesiotemporal/hippocampal restricted diffusion may be seen with transient global amnesia, 2 this case is of special interest mechanistically although we cannot exclude the alternative hypothesis that the episode of TGA resulted in the Tako-tsubo cardiomyopathy which subsequently caused the cardioembolic shower. References: Stollberger C, DeCillia N, Finsterer J. 'Tako-tsubo cardiomyopathy with transient global amnesia and cerebellar embolic stroke triggered by existential fear.' Neurol Neurochir Pol 2018; 52(3):394–396. Enzinger C, Thimary F, Kapeller P, Ropele S, Schmidt R, Ebner F, Fazekas F. 'Transient global amnesia: diffusion-weighted imaging lesions and cerebrovascular disease.' Stroke 2008;39(8):2219–2225.